Empowering academic essay writing through project-based learning: A case study of non-English major students in Institut Teknologi dan Bisnis Asia Malang - Aqromi, Nur Lailatul; Wahyuni, Tri (Journal of English Language Teaching and Learning (JETLE), 2025)
This case study investigated how Project-Based Learning (PBL) supported academic essay writing among non-English major undergraduates in an English for Specific Purposes (ESP) course at Institut Teknologi dan Bisnis Asia Malang (N = 32, Information Technology). Methodologically, the study contributed a transparent analytic protocol that combined pre post analytic rubric scoring, classroom observations, weekly reflection journals, and focus-group discussions, with procedures for coding, theme development, member checking, and an audit trail to enhance trustworthiness. The four-week PBL intervention culminated in a digital magazine on the “AI Phenomenon” and scaffolded five writing components: content, structure/organization, argumentation, cohesion, and language use. Descriptive comparisons showed gains across components on a 5-point scale, with structure/organization (+1.04) and cohesion (+1.15) indicating stronger organization and clearer reader guidance. Thematic synthesis of qualitative sources triangulated these results, evidencing increased writer confidence, clearer uptake of feedback, and engagement driven by an authentic publication target. Contextually, the study documented an actionable PBL model for ESP settings with novice EFL writers, detailing design principles such as authentic product, iterative peer review aligned with analytic rubrics, and reflective documentation. The study argued that PBL provided a structured pathway from formulaic drafting toward audience aware, coherent academic essays.